"I see what you're saying": examining self-disclosure and nonverbal communication in digital environments - Walsh, Adam Clark, author; Martey, Rosa, advisor; Long, Marilee, committee member; Marx, Nick, committee member (Colorado State University. Libraries, 2018)
Computer-mediated environments are comfortable spaces for people to engage in interpersonal communications. By building on the theoretical arguments of computer-mediated communication scholars (Joinson, 2001; Walther, 2008), this study used a secondary dataset from the SCRIBE project, to examine chat transcripts in a content analysis. The study explored the role of self-disclosure and 15 different nonverbal cues in interpersonal communications in World of Warcraft (WoW). For the SCRIBE project, teams of 3-4 players were tasked with saving the digital city, Dalaran, from marauders (Reene et al., 2011). After gathering all SCRIBE project WoW chat transcripts, a 30% sample was used in a content analysis for self-disclosure statements. These self-disclosure statements and nonverbal cue data (collected in the SCRIBE project) were combined using statistical software, and examined with Pearson correlations, multiple linear regressions, and hierarchical regressions to show relationships. Results supported previous literature in computer-mediated interpersonal communications (Joinson, 2001), and Walther's (2008) Social Information Processing Theory (SIPT), to show players share self-disclosure statements and translate nonverbal cues for sharing relational information between players. The implications for this study are important for understanding how the interpersonal communication concepts, self-disclosure and nonverbal cues, manifest in video games such as WoW, and work together in the communication process. Future research should examine when self-disclosure statements and nonverbal cues are used in relation to the overall communication process, and expand on key dimensions of Walther's SIPT.